Cry pretty - Underwood, Carrie, 1983- (Nashville, TN Capitol Records Nashville, 2018)
Seven-time Grammy Award winning superstar Carrie Underwood is back with a brand new studio album. The first single, which is also the title track, has quickly been making its way up to the top of the country charts.
Cry pretty -- Ghosts on the stereo -- Low -- Backsliding -- Southbound -- That song that we used to make love to -- Drinking alone -- The bullet -- Spinning bottles -- Love wins -- End up with you -- Kingdom -- The champion (featuring Ludacris) (bonus track).
Title from disc label.
Compact disc.
Lyrics printed on insert.
Produced by David Garcia and Carrie Underwood.
Carrie Underwood ; with accompaniment.
108588
Keywords: 2011-2020; Country music -- 2011-2020.; Music CDs